QUALITY ASSESSMENT OF SCHEDULE OPTIMIZATION OF URBAN PASSENGER TRANSPORT ON DUPLICATING STRETCHES - Кравченя, Ирина; Ворона, Анна (SWorldJournal, 2022)
The article presents the optimization problem of public transport schedule in response to the improvement in passenger service quality. Using scheduling technique of route vehicles on duplicating stretches allows to determine the optimal vehicle traffic i